2010
DOI: 10.1007/s00425-010-1297-4
|View full text |Cite
|
Sign up to set email alerts
|

Betaine aldehyde dehydrogenase genes from Arabidopsis with different sub-cellular localization affect stress responses

Abstract: Arabidopsis thaliana belongs to those plants that do not naturally accumulate glycine betaine (GB), although its genome contains two genes, ALDH10A8 and ALDH10A9 that code for betaine aldehyde dehydrogenases (BADHs). BADHs were initially known to catalyze the last step of the biosynthesis of GB in plants. But they can also oxidize metabolism-derived aminoaldehydes to their corresponding amino acids in some cases. This study was carried out to investigate the functional properties of Arabidopsis BADH genes. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 76 publications
8
80
0
1
Order By: Relevance
“…The results showed that ScBADH transcripts could be induced by ABA, PEG, and especially, NaCl treatments. These results are similar to those obtained in rice but different to those obtained in Arabidopsis (Niu et al, 2007;Missihoun et al, 2011), indicating that ScBADH may be involved in signal transduction in response to salt in S. corniculata. Missihoun et al (2011) showed that young and adult plants lacking ALDH10A8 transcripts were drought and salt sensitive.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results showed that ScBADH transcripts could be induced by ABA, PEG, and especially, NaCl treatments. These results are similar to those obtained in rice but different to those obtained in Arabidopsis (Niu et al, 2007;Missihoun et al, 2011), indicating that ScBADH may be involved in signal transduction in response to salt in S. corniculata. Missihoun et al (2011) showed that young and adult plants lacking ALDH10A8 transcripts were drought and salt sensitive.…”
Section: Discussionsupporting
confidence: 77%
“…These results are similar to those obtained in rice but different to those obtained in Arabidopsis (Niu et al, 2007;Missihoun et al, 2011), indicating that ScBADH may be involved in signal transduction in response to salt in S. corniculata. Missihoun et al (2011) showed that young and adult plants lacking ALDH10A8 transcripts were drought and salt sensitive. Similar results were found in sweet potato, in which those expressing spinach BADH had improved stress tolerance (Fan et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, some low-BALaffinity isoenzymes lack the peroxisomal signal. They may be located in leucoplasts, as was recently found for one of the two low-BAL-affinity isoenzymes from Arabidopsis (Missihoun et al, 2011). The rest of the low-BAL-affinity isoenzymes have an SKL or SKL-like C-terminal tripeptide.…”
Section: Discussionmentioning
confidence: 61%
“…The physiological functions of a number of enzymes and metabolic pathways indicated by proteomic data have been verified. Examples include the oxidative pentose phosphate pathway (Meyer et al, 2011), betaine aldehyde dehydrogenase (Missihoun et al, 2011), SDRa (Wiszniewski et al, 2009), and the bifunctional transthyretin-like protein involved in purine catabolism and S-allantoin biosynthesis (Lamberto et al, 2010), which have significantly broadened our knowledge of peroxisome metabolism.…”
Section: Experimental Proteomicsmentioning
confidence: 99%